PENGARUH UPAH MINIMUM DAN PENGANGGURAN TERHADAP PERTUMBUHAN EKONOMI DI PROVINSI ACEH - Anggia Lestari Lubis; Murtala Murtala (LPPM UNIMAL, 2021)
This study examined the effect of the Provincial Minimum Wage and the unemployment rate on Economic Growth in Aceh Province. The data used in this study were data from 2006 to 2020. The analysis method used was multiple linear data regression with the help of E-Views 10. The results showed that the Provincial Minimum Wage positively and significantly economic growth in Aceh Province and the unemployment rate did not have a significant and positive effect on the level of economic growth in Aceh Province